PENDEKATAN RGEC DALAM PENGUKURAN KESEHATAN PERBANKAN SELAMA PANDEMI COVID-19 - Shofwan; Heryanto, Nadira Nur Affifah (Contemporary Studies in Economic, Finance and Banking, 2024)
In 2020, there was a decrease in the net profit of state-owned banks by an average of 40% for each bank, followed by an increase in the potential for credit risk and a decrease in the share price of state-owned banks. In maintaining the level of public trust, banks must continue to maintain their level of health. This level of health can be calculated through RGEC (Risk Profile, Good Corporate Governance, Earning and Capital) calculation analysis. The method used is descriptive comparative, namely by examining annual financial reports which are then compared with other reports so that differences in the soundness level of banks and state-owned banks are known during the Covid-19 pandemic. The results of this study show difference in the level of soundness every year during the COVID-19 pandemic from 2020 to 2022 at state-owned banks as indicated by changes in RGEC calculation ratios.